A microfluidic paper-based analytical device for the assay of albumin-corrected fructosamine values from whole blood samples. (January 2015) - Boonyasit, Yuwadee; Laiwattanapaisal, Wanida
Background: A method for acquiring albumin-corrected fructosamine values from whole blood using a microfluidic paper-based analytical system that offers substantial improvement over previous methods is proposed.Results: The time required to quantify both serum albumin and fructosamine is shortened to 10 min with detection limits of 0.50 g dl -1 and 0.58 mM, respectively (S/N = 3). The proposed system also exhibited good within-run and run-to-run reproducibility. The results of the interference study revealed that the acceptable recoveries ranged from 95.1 to 106.2%. The system was compared with currently used large-scale methods (n = 15), and the results demonstrated good agreement among the techniques.Conclusion: The microfluidic paper-based system has the potential to continuously monitor glycemic levels in low resource settings.